AS-AD in the standard dynamic neoclassical model: Business cycles and growth trends - Max Gillman (Cardiff University, Cardiff Business School, 2012)
The paper shows how a dynamic neoclassical AS-AD can be derived and used to describe business cycles and growth trends to undergraduates. Derived within the Ramsey-Cass-Koopmans (RCK) model, the AS-AD is the stationary equilibrium of the deterministic dynamic general equilibrium framework. Allowing Solow exogenous growth, the AS-AD is derived along the balanced growth path equilibrium. The derivation first builds consumption demand, aggregate demand, and then aggregate supply through the equilibrium conditions and a closed form solution for the capital stock. Through a comparative static change in goods sector productivity, the paper shows the basic failing of the standard RBC model. Allowing a second comparative static change in the consumer's time endowment, this captures a change in the external margin of labor supply. These comparative statics enable explanation of the business cycle, and Solow-plus growth trends including education time and working time. In extension of RCK, the paper shows beyond the undergraduate level, how to derive AS-AD when including human capital and endogenous growth. This allows an endogenous change in the time endowment for work and leisure through a change in human capital productivity, with a similar but more fundamental AS-AD story of business cycles and growth trends.
Keywords: A22; A23; E13; 330; Ramsey-Cass-Koopmans; supply; demand; state variable